Requirements for balance setting-up and report improvement possibilities - Gipiene, G.; Matuseviciene, L. (Економічний вісник Донбасу, 2010)
Object of the article research is balance report. A theoretical research is done in the article where requirements of international and Lithuanian acts for balance content and form making are compared and differences between them are presented. Because it is assessed that balance is not informative enough balance improvement possibilities are introduced in the article by the authors. The article consists of introduction, two chapters, conclusion, and references. Key words: balance, IAS 1, Fourth Council Directive, BAS 2, improvement of balance sheet.